Comparing Pre-service Civic Education Teachers’ TPACK Confidence Across Course Modes - Imam Fitri Rahmadi; Eti Hayati; Aulia Nursyifa (Research in Social Sciences and Technology- OpenED Network, 2020)
Integrating technology into learning and instruction processes is inevitable in this modern world, so it is of pivotal importance that all teachers should master TPACK confidently. Unfortunately, the approaches toward teacher education programs in many countries, specifically in Indonesia, do not yet integrate TPACK in the curriculum. This study aimed at comparing pre-service civic education teachers’ TPACK confidence across three course modes—Regular A, B, and C—of a pre-service teacher education program in Indonesia. Involving 90 pre-service civic education teachers, a self-report measure survey is used as the research method. The result revealed that Regular A and C pre-service civic education teachers report an almost equal level of TPACK confidence while the Regular B pre-service civic education teachers report a lower level of TPACK confidence. Academic and practical implications of these findings are discussed, and insights for future teacher education programs are provided.